DOP86 Subcutaneous infliximab (CT-P13 SC) as maintenance therapy for Crohn's disease: A phase 3, randomised, placebo-controlled study (LIBERTY-CD). (30th January 2023) - Colombel, J F; Hanauer, S B; Sandborn, W; Sands, B E; Schreiber, S; Danese, S; Kierkus, J; Kulynych, R; Klopocka, M; Lahat, A; Gonciarz, M; Osipenko, M; et al.
Abstract: Background: CT-P13 subcutaneous (SC) infliximab formulation showed comparable efficacy and safety with CT-P13 intravenous (IV) infliximab in inflammatory bowel disease (IBD) 1 and rheumatoid arthritis 2 . This study aimed to demonstrate the superiority of CT-P13 SC over placebo as maintenance therapy after induction therapy of CT-P13 IV in patient with Crohn's disease (CD). Methods: Moderately to severely active CD patients with Crohn's disease activity index (CDAI) score 220 to 450 and simplified endoscopic activity score for Crohn's disease (SES-CD) of ≥6 points for ileal-colonic CD or ≥4 points including ulcer score from at least 1 segment for ileal CD or colonic CD were enrolled LIBERTY-CD study (NCT03945019) and treated with open-label CT-P13 IV 5 mg/kg at Weeks 0, 2 and 6 as induction therapy. At Week 10, patients who had a clinical response were randomised (2:1) to receive either CT-P13 SC 120 mg (CT-P13 SC) or placebo every 2 weeks up to Week 54. At Week 54, clinical remission and endoscopic response were assessed as co-primary endpoints. Clinical response, clinical remission (alternative definition), endoscopic remission, and corticosteroid-free remission were assessed at Week 54 as key secondary endpoint. Safety was evaluated up to Week 54. Results: A total of 396 patients were enrolled and 343 patients (86.6%) were randomised (231 in CT-P13 SC arm and 112 in placebo arm) at Week 10. At Week 54, the clinical remission rate was greater in CT-P13 SC arm than placebo arm (62.3% and 32.1% respectively, with P <0.0001). The endoscopic response rate was also greater in CT-P13 arm than placebo arm (51.1% and 17.9% respectively, with P <0.0001). CT-P13 SC also had significantly greater efficacy on key secondary endpoints results compared to placebo arm (Table 1). Safety profiles were generally comparable between CT-P13 SC and placebo arms, but a single death was reported during the maintenance phase (Table 2). Conclusion: CT-P13 SC was more effective than placebo in clinical remission, endoscopic response, clinical response, clinical remission (alternative definition), endoscopic remission, and corticosteroid-free remission at Week 54. No new safety concerns were found during treatment of CT-P13 SC. These results demonstrate that maintenance therapy with CT-P13 SC provides both a robust clinical benefit and the convenience of SC administration to moderately to severely active CD patients. [1] Schreiber et al., 2021. Gastroenterology 2021;160:2340–23 [2] Westhovens et al., 2020. Rheumatology 2020;00:1